Pengaruh Budaya Sekolah dan Supervisi Akademik Kepala Sekolah Terhadap Peningkatan Kinerja Guru di Sekolah Dasar Gugus Hasanudin Kecamatan Kaliori Kabupaten Rembang - Nunuk Kristiningsih; Ahmad Hilal Madjdi; Suad Suad (Peneliti.net, 2022)
The results of the study 1) There is an influence of school culture on teacher performance at SD Gugus Hasanudin, Kaliori District, Rembang Regency, this is based on a significance value of 0.000 <0.05. While the value of Fcount is 254.551 > Ftable 4.03. The magnitude of the effect is based on the Rsquare value of 0.833. This result means that 83.3% of teacher performance in SD Gugus Hasanudin, Kaliori District, Rembang Regency is influenced by school culture while the remaining 16.7% is influenced by other factors. 2) There is an effect of the principal's academic supervision on the performance of teachers in Hasanudin Elementary School, Kaliori District, Rembang Regency, this is based on a significance value of 0.000 <0.05. While the value of Fcount 290.002 > Ftable 4.03. The magnitude of the effect is based on the Rsquare value of 0.850. This result means that 85% of teacher performance in Hasanudin Elementary School, Kaliori District, Rembang Regency is influenced by the academic supervision of the principal. While the remaining 15% is influenced by other factors. 3) There is a significant difference between the influence of school culture and principal's academic supervision on teacher performance based on the influence of school culture on teacher performance of 83.3% while the influence of principal's academic supervision on teacher performance is 85%. These results indicate that the influence given by the supervision of the principal is greater than the influence of school culture (85 > 83.3).